2019
DOI: 10.3389/fphys.2019.00919
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Bleaching Products With Up to 6% and With More Than 6% Hydrogen Peroxide: Whitening Efficacy Using BI and WID and Side Effects – An in vitro Study

Abstract: The aim of this study was to evaluate the effect of bleaching agents containing different concentrations of hydrogen peroxide (HP) on color-change and on enamel-surface in bovine teeth. Furthermore the influence on cell viability and proliferation was investigated. Two hundred and forty teeth were randomly assigned into four groups (home bleaching ≤6%, in-office bleaching ≤6%, in-office bleaching > 6% HP, and control group). Bleaching was performed after artificial staining and the bleached index (BI) as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 47 publications
(57 reference statements)
6
22
0
1
Order By: Relevance
“…Many studies, including the present study, have found the Philips Zoom bleaching system to be more effective than the Opalescence Boost PF bleaching system. [44][45][46] In addition, consistent with our results, Lee et al found a slight reduction in the color change after 1 month with both Philips Zoom and Opalescence Boost PF. 44 The Philips Zoom bleaching system exhibits high bleaching effectiveness because of a photoinitiator, ferrous gluconate, inside the gel, which accelerates the breakdown of HP due to UV light (Zoom Advanced Power) and provides effective bleaching by increasing the amount of OH radicals with the Fenton reaction.…”
Section: Discussionsupporting
confidence: 92%
“…Many studies, including the present study, have found the Philips Zoom bleaching system to be more effective than the Opalescence Boost PF bleaching system. [44][45][46] In addition, consistent with our results, Lee et al found a slight reduction in the color change after 1 month with both Philips Zoom and Opalescence Boost PF. 44 The Philips Zoom bleaching system exhibits high bleaching effectiveness because of a photoinitiator, ferrous gluconate, inside the gel, which accelerates the breakdown of HP due to UV light (Zoom Advanced Power) and provides effective bleaching by increasing the amount of OH radicals with the Fenton reaction.…”
Section: Discussionsupporting
confidence: 92%
“…18 However, the CIELAB formulation is widely used in many studies evaluating tooth colour. 9,16,43 For this reason, in our study the CIELAB and CIEDE2000 formulae were used together to evaluate colour change. Paravina et al 17 reported the perceptibility threshold ΔE ab = 1.2 and the acceptability threshold ΔE ab = 2.7 in the CIELAB system.…”
Section: Colour Evaluationmentioning
confidence: 99%
“…( 1 , 3 , 4 , 7 - 11 ). Approximately one third of CP decomposes to HP, which is the active agent of bleaching ( 1 , 4 , 8 , 9 , 12 ). Peroxides are unsTable substances that, in contact with dental tissues and moisture, release free radicals such as oxygen ions, which have the ability to diffuse through enamel and dentin and cause the oxidation of pigmented molecules that cause the tooth structure to darken ( 4 , 6 , 8 , 11 - 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies ( 1 , 4 ) have related that high concentration of CP and HP bleaching gels used for a shorter time did not show negative effects on enamel, while low concentration gels of peroxides caused changes on enamel surface such as decrease in its hardness and increased surface roughness. However, other studies ( 17 , 18 ) related that all the bleaching agents reduced the enamel hardness and increased the surface roughness, and that changes caused by products with high concentrations do not differ substantially from those caused by low concentrations, these discrepancies can occur due to different models of applied studies ( 4 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation